2013
DOI: 10.1021/la402669z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin Effects on Membrane Structure and Dynamics

Abstract: Cardiolipin (CL) is a lipid with unique properties solely found in membranes generating electrochemical potential. It contains four acyl chains and tends to form nonlamellar structures, which are believed to play a key role in membrane structure and function. Indeed, CL alterations have been linked to disorders such as Barth syndrome and Parkinson's disease. However, the molecular effects of CL on membrane organization remain poorly understood. Here, we investigated the structure and physical properties of CL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 60 publications
8
116
0
Order By: Relevance
“…For instance, SM has been proposed as the putative receptor for lysenin, a toxin from the earthworm Eisenia fetida (Yamaji-Hasegawa et al 2003), and for actinoporins, which are toxins from sea anemones (Á lvarez et al 2009;García-Ortega et al 2011). CL has been suggested to be essential for Bcl-2 proteins function during apoptosis, thereby participating in the regulation of programed cell death (Cosentino and García-Sáez 2014;Unsay et al 2013), and Cyt d-endotoxins seem to recognize unsaturated lipids (Thomas and Ellar 1983).…”
Section: Structural Classification Of Pfpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, SM has been proposed as the putative receptor for lysenin, a toxin from the earthworm Eisenia fetida (Yamaji-Hasegawa et al 2003), and for actinoporins, which are toxins from sea anemones (Á lvarez et al 2009;García-Ortega et al 2011). CL has been suggested to be essential for Bcl-2 proteins function during apoptosis, thereby participating in the regulation of programed cell death (Cosentino and García-Sáez 2014;Unsay et al 2013), and Cyt d-endotoxins seem to recognize unsaturated lipids (Thomas and Ellar 1983).…”
Section: Structural Classification Of Pfpsmentioning
confidence: 99%
“…Indeed, CL seems to allow specific targeting of tBid to mitochondria and to promote tBid binding with interaction partners such as BclxL (Lutter et al 2000). Thus, activation of Bax by tBid takes place in cooperation with CL and results in pore formation leading to the release of apoptotic factors (Cosentino and García-Sáez 2014;Kuwana et al 2002;Unsay et al 2013). One should also keep in mind that the CL enrichment observed in the outer mitochondria membrane during apoptosis not only promotes local alterations in membrane curvature but also in charge, which may facilitate the recruitment of Bcl-2 proteins to mitochondria (Cosentino and García-Sáez 2014).…”
Section: The Pro-apoptotic Protein Baxmentioning
confidence: 99%
“…They are prepared using various techniques like vesicle deposition, Langmuir-Blodgett method and spin-coating 8,9 . AFM imaging has been used to follow the formation of these supported bilayers 10 , and probe different structures formed by membranes of different compositions [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…CL is a mitochondrial-specific phospholipid that contributes 12-17 % of the total mitochondrial phospholipid content, present largely in the inner membrane (14-23 %) and a smaller proportion in the outer membrane (3-10 %) [61]. Conical-shaped CL has a non-bilayer forming propensity and may facilitate the formation of an intermediate state during membrane remodelling events including fission and fusion [62][63][64][65]. A direct interaction between Drp1 and CL-containing membranes was observed in vitro using a Trp-Dansyl FRET assay [60] whereas lipid dot-blot analysis found that direct Drp1-CL interactions were mediated by four lysine residues in the InsB region of Drp1 that are conserved among vertebrates [59] Disruption of an essential cardiolipin synthase gene (cls-1) in Arabidopsis thaliana leads to a block in fission resulting in unbiased fusion [64].…”
Section: Drp1 Cardiolipin and Reactive Oxygen Speciesmentioning
confidence: 99%